15N MRI of SLIC‐SABRE Hyperpolarized 15N‐Labelled Pyridine and Nicotinamide. Issue 36 (27th May 2019) - Svyatova, Alexandra; Skovpin, Ivan V.; Chukanov, Nikita V.; Kovtunov, Kirill V.; Chekmenev, Eduard Y.; Pravdivtsev, Andrey N.; Hövener, Jan‐Bernd; Koptyug, Igor V.
Abstract: Magnetic Resonance Imaging (MRI) is a powerful non‐invasive diagnostic method extensively used in biomedical studies. A significant limitation of MRI is its relatively low signal‐to‐noise ratio, which can be increased by hyperpolarizing nuclear spins. One promising method is Signal Amplification By Reversible Exchange (SABRE), which employs parahydrogen as a source of hyperpolarization. Recent studies demonstrated the feasibility to improve MRI sensitivity with this hyperpolarization technique. Hyperpolarized 15 N nuclei in biomolecules can potentially retain their spin alignment for tens of minutes, providing an extended time window for the utilization of the hyperpolarized compounds. In this work, we demonstrate for the first time that radio‐frequency‐based SABRE hyperpolarization techniques can be used to obtain 15 N MRI of biomolecule 1‐ 15 N‐nicotinamide. Two image acquisition strategies were utilized and compared: Single Point Imaging (SPI) and Fast Low Angle SHot (FLASH). These methods demonstrated opportunities of high‐field SABRE for biomedical applications. Abstract : Signal amplification by reversible exchange hyperpolarization of biomolecules was carried out in situ in a MRI scanner. Thus 15 N MRI of 15 N‐pyridine and 1‐ 15 N‐nicotinamide was performed using two different pulse sequences: Single Point Imaging and Fast Low Angle SHot (FLASH). The method is a promising approach for biomedical applications.